2018
DOI: 10.1039/c7gc02118f
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl carbonate: a versatile reagent for a sustainable valorization of renewables

Abstract: Dimethyl carbonate (DMC) is an environmentally sustainable compound which can be used efficiently for the upgrading of several promising renewables including glycerol, triglycerides, fatty acids, polysaccharides, sugar-derived platform molecules and lignin-based phenolic compounds. This review showcases a thorough overview of the main reactions where DMC acts as a methylating and/or methoxycarbonylating agent for the transformation of small bio-based molecules as well as for the synthesis of biopolymers. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
138
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(139 citation statements)
references
References 166 publications
0
138
0
1
Order By: Relevance
“…[42] The oxidationo fp ropylene to PO (Scheme2,r oute c) can be carried out by am ore environmentally friendly process employing at itaniums ilicate catalyst( TS-1) and hydrogen peroxide as the oxidant. [48] The synthesis of DMC from EC and methanol has been highlighted as most sustainable among several possible routes in terms of global warming impact. [44] It hasb een proposed that am ore sustainable synthesis of EC could be carried out by starting from bioethanol (i.e.,e thanol produced from biomass) followed by its dehydration [45] to afford bio-ethylene (Scheme 2, route d).…”
Section: Unfunctionalized Cyclic Carbonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] The oxidationo fp ropylene to PO (Scheme2,r oute c) can be carried out by am ore environmentally friendly process employing at itaniums ilicate catalyst( TS-1) and hydrogen peroxide as the oxidant. [48] The synthesis of DMC from EC and methanol has been highlighted as most sustainable among several possible routes in terms of global warming impact. [44] It hasb een proposed that am ore sustainable synthesis of EC could be carried out by starting from bioethanol (i.e.,e thanol produced from biomass) followed by its dehydration [45] to afford bio-ethylene (Scheme 2, route d).…”
Section: Unfunctionalized Cyclic Carbonatesmentioning
confidence: 99%
“…To note, EC can react with methanol to afford DMC (Scheme 2, route f), which is ab enign and nontoxic carbonylation reagent. [48] The synthesis of DMC from EC and methanol has been highlighted as most sustainable among several possible routes in terms of global warming impact. [1c] Unfunctionalized saturated carbonates can be used for the synthesis of polymers by nucleophilic ring opening with diamines leading to bis-hydroxycarbamates as starting materials for isocyanatefree polyester polyurethanes.…”
Section: Unfunctionalized Cyclic Carbonatesmentioning
confidence: 99%
“…It is not even necessary to separate the unreacted DMC, since it can be used as an additive for fossil diesel, due to the high oxygen content of the molecule. In fact, the DMC is attracting the interest of researchers due to the increasing importance of environmental and resource issues to the realization of a sustainable society through a green chemistry activity development [243][244][245][246][247][248][249].…”
Section: Biodiesel-like Biofuels That Integrate the Glycerol As Glycementioning
confidence: 99%
“…In connection to the wide-ranging interests of our group in developing biomass-derived platform chemicals [21][22][23][24][25][26], we recently reported a fundamental study on the photoreduction of methyl viologen using a set of citric acid-derived CDs, paving the way towards the rational design of carbon-nanoparticles for efficient photocatalytic organic transformations [27]. These studies demonstrated that the carbon-nitrogen source, the synthetic method, and the resulting structural properties strongly affect the electrochemical properties of CDs and thus their photo-reactivity.…”
Section: Introductionmentioning
confidence: 99%